A survey of empirical literature on hedge fund performance - Fan Yang (Charles University in Prague, Institute of Economic Studies (IES), 2020)
This paper reviews recent developments in empirical literature analyzing hedge fund performance. Popularity of hedge funds as an investment device has dramatically increased over the past decades. This prompted extensive academic research examining their performance. Systematic examination of hedge fund performance is plagued by the opaqueness of their operations, which complicates risk measurement, and by the lack of well-regulated systematic disclosure, which makes it difficult to obtain comprehensive bias-free data sets. Thus, various studies reach divergent conclusions about hedge funds' ability to benefit from investment managers' prowess in generating superior return. We survey this literature and classify it into several streams based on the underlying performance drivers. We compare and contrast conclusions of individual articles and conclude that even though there is little consensus on the magnitude and significance of hedge fund outperformance most published studies seem to suggest that hedge funds earn at least the excess return to cover the fees they charge. The relationship between the regulation and performance is complex but more stringent regulation seems to reduce managerial misreporting.
Keywords: G12; G28; 330; hedge fund; literature; review; survey